Public officials associations and professionalism - Plant, Jeremy F.; Arnold, David S. (1993)
Associations of public officials have been an important element of public professionalism in the United States since the reform era. This paper examines the ways in which associations of public officials are helping to redefine public professionalism. The focus on the paper is on the promotion of professionalism by association activities, the sense of professional identity fostered by association involvement, and the ways in which associations integrate issues of policy, management, and professional expertise to contribute to the development of true public professionalism.
Keywords: Public administration - U.S.A.; Civil service - U.S.A.